2000
DOI: 10.1111/j.1751-9861.2000.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Fitness Predicts Daily Coping Better Than Physical Activity

Abstract: One hundred sixty‐six participants (70 males, 96 females) completed a series of questionnaires measuring perceived fitness, social desirability, self‐esteem, hope, and perceived stress levels and coping abilities. Participants were then given an activity monitoring device to wear for 1 week. Participants recorded daily measures of physical activity, perceived fitness, and perceived stress and coping over 7 days. Results revealed that although perceived physical fitness was reliably associated with coping, actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
3
19
0
1
Order By: Relevance
“…It further confirms laboratory studies that found reduced stress reactivity among participants with high exercise or fitness levels 38) . Moreover, this finding accords with the notion that self-rated fitness is negatively related to daily stress 15) . Also, perceived fitness explains significant variance in the psychological and physiological reactivity to laboratory stress beyond that attributable to estimated aerobic physical fitness 18,32) .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It further confirms laboratory studies that found reduced stress reactivity among participants with high exercise or fitness levels 38) . Moreover, this finding accords with the notion that self-rated fitness is negatively related to daily stress 15) . Also, perceived fitness explains significant variance in the psychological and physiological reactivity to laboratory stress beyond that attributable to estimated aerobic physical fitness 18,32) .…”
Section: Discussionsupporting
confidence: 80%
“…This new focus is warranted because in previous studies, self-rated fitness was more closely related to mental health and daily stress than objective fitness measures 15) . This suggests that some of the positive emotional results associated with exercise may occur because of the psychological gains from the experience of trying to get fit or believing that one is fit rather than from an increase in aerobic physical fitness 16) .…”
Section: Abstract: Perceived Fitness Protects Against Stress-based Mementioning
confidence: 99%
See 1 more Smart Citation
“…Perceived physical fitness was measured with one item ranging from 1 (very poor fitness) to 10 (excellent fitness) (30). This measure has proved to be correlated with measures of objective physical fitness and perceived well-being (29).…”
Section: Psychometric Measuresmentioning
confidence: 99%
“…Self-perceived fitness does accurately correlate with objective measurements of fitness (Lamb 1992) and each of our interviewees perceived their fitness to have increased. It is also important to note that perceived fitness has been found to be a more accurate measurement of "daily coping" than actual fitness (Plante et al 2000). There is potential for future research to build upon these findings firstly by exploring the interplay between perceived and actual fitness and also mood state for this cohort and secondly by measuring levels of flexibility and self-perceived pain.…”
Section: Discussionmentioning
confidence: 91%